Mediastinal Schistosomiasis in a Patient with HIV and Leprosy: A Case Report - Diksha Sabharwal; Asmita Samal; Kalyan Kumar Reddy; Sonali Agarwal (Journal of Clinical and Diagnostic Research)
Schistosomiasis is a parasitic disease commonly affecting the urinary and gastrointestinal systems, caused by trematode worms of the genus Schistosoma. Mediastinal involvement is an exceedingly rare presentation, particularly in immunocompromised individuals such as those with Human Immunodeficiency Virus (HIV). Hereby, the authors present a case report of 51-year-old male, known to have HIV and on antiretroviral therapy, with a history of Borderline Tuberculoid (BT) leprosy, presented with sudden-onset breathlessness, chest pain, and dysphagia. Diagnostic imaging and bronchoscopy revealed the presence of Schistosoma haematobium in the mediastinum. The patient was treated with praziquantel and broad-spectrum antibiotics to manage the parasitic infection and prevent secondary bacterial complications. His condition required a multidisciplinary approach due to the complexity of his co-existing conditions. The patient responded well to a combination of praziquantel and broad-spectrum antibiotics. Praziquantel remains the treatment of choice for schistosomiasis, while antibiotics were necessary to prevent secondary infections in this immunocompromised patient. Close monitoring and follow-up were essential to ensure treatment success and to manage potential complications. This case illustrates the complexities of diagnosing and managing rare parasitic infections in patients with multiple chronic conditions. Early recognition, appropriate diagnostic work-up, and targeted therapy are critical to improving outcomes in such challenging cases. This report adds to the limited literature on mediastinal schistosomiasis and highlights the importance of a multidisciplinary approach in managing such patients.